2013
DOI: 10.2174/138161281939131127120517
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective Effects of Sour Cherry Seed Extract (SCSE) on the Hypercholesterolemic Rabbit Heart

Abstract: This study demonstrates SCSE cardioprotective effects on hypercholesterolemic hearts. Correlation of these outcomes with HO-1 expression suggests that the effect may be mediated by activity of this enzyme. However, definitive proof of HO-1 dependence requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 0 publications
4
29
0
1
Order By: Relevance
“…These outcomes are consistent with many investigations demonstrating that phytochemical HO-1 induction correlates with improved prognoses of many diseases (12).We have previously shown that SCSE strongly protects the heart against I/R injury, as revealed by enhanced postischemic left ventricle function, reduced infarct size, and decreased apoptosis in rat hearts subjected to I/R-injury (13). Recent animal studies also demonstrated SCSE-mediated enhancement of SCSE-mediated adaptive response in hearts of hypercholesterolemic rabbits (14). In related in vitro studies, SCSE-induced upregulation of HO-1 by human leukocytes, suppressed lipopolysaccharide (LPS)-mediated expansion of CD3+TNF-α+ and CD3+IL8+ subpopulations more significantly than in cells from healthy individuals in blood from type 2 diabetics (15).…”
Section: A C C E P T E Dsupporting
confidence: 89%
“…These outcomes are consistent with many investigations demonstrating that phytochemical HO-1 induction correlates with improved prognoses of many diseases (12).We have previously shown that SCSE strongly protects the heart against I/R injury, as revealed by enhanced postischemic left ventricle function, reduced infarct size, and decreased apoptosis in rat hearts subjected to I/R-injury (13). Recent animal studies also demonstrated SCSE-mediated enhancement of SCSE-mediated adaptive response in hearts of hypercholesterolemic rabbits (14). In related in vitro studies, SCSE-induced upregulation of HO-1 by human leukocytes, suppressed lipopolysaccharide (LPS)-mediated expansion of CD3+TNF-α+ and CD3+IL8+ subpopulations more significantly than in cells from healthy individuals in blood from type 2 diabetics (15).…”
Section: A C C E P T E Dsupporting
confidence: 89%
“…(1) The observed stability throughout the evaluation period of heart rates, respiratory frequencies, M-mode and Doppler measurements demonstrate that basal cardiopulmonary activity was not substantially disrupted by hypercholesteremia, an outcome for which preliminary evidence was provided by an earlier study conducted in the laboratory of the authors [28]. …”
Section: Discussionmentioning
confidence: 87%
“…Proposed resolution for this challenge is summarized below in Limitations and proposed solutions. We previously demonstrated that SCE, administered orally to animals, induces HO-1 expression at levels that inhibit and reverse ischemia-reperfusion injury to the retina (Szabo et al 2004) and heart (Bak et al 2006;Juhasz et al 2013), with topical application exhibiting powerful photoprotective effects on skin and negligible toxicity, even at whole-body dosage in excess of 200× therapeutic levels (Bak et al 2011).…”
Section: Effect Of Topical Application Of Sce Emulsion On Serum C-reamentioning
confidence: 99%
“…These encouraging findings further suggest future potential for clinical use of this plant material. The results of ongoing work by our laboratory (Mahmoud et al 2013(Mahmoud et al , 2014Bak et al 2006Bak et al , 2010Bak et al , 2011Szabo et al 2004;Juhasz et al 2013;Lekli et al 2014) and others (Haines et al 2012;Morse and Choi 2002) are consistent with recent demonstrations that inducers of HO-1 may radically improve prognoses of many diseases in which oxidative stress is a primary pathomechanism, particularly disorders of the cardiovascular system, lung, neurological tissue, and kidney (Haines et al 2012). Strategies for therapeutic induction of the enzyme are increasingly viewed by clinicians as a primary approach to prevention and management of an expanding range of serious chronic illness (Morse and Choi 2002).…”
Section: Effect Of Topical Application Of Sce Emulsion On Serum C-reamentioning
confidence: 99%